SEBUAH TELAAH ATAS REGULASI DAN PENETAPAN PENGAMPUAN BAGI PENYANDANG DISABILITAS DI INDONESIA DALAM PARADIGMA SUPPORTED DECISION MAKING - PUSPANINGTYAS PANGLIPURJATI (Jurnal Paradigma Hukum Pembangunan, 2021)
Kitab Undang-Undang Hukum Perdata regulates that an adult, who is in a continuous state of simple-mindedness, insanity or rage, shall be placed under conservatorship, notwithstanding that he might have mental capacity from time to time (mental disabilities). Similiar to that, Undang-Undang Penyandang Disabilitas regulates that people with disabilities can be declared as incapable of the law and placed under conservatorship by court judgment. The consequence of that conservatorship is an individual placed in conservatorship has no legal capacity and prohibited to do any legal action by themself. The perspective that be used in that two regulations and some court judgments in giving conservatorship is substituted decision making which the conservator substitutes the position of an individual placed in conservatorship. This concept actually is no longer appropriate with the new paradigm brought by CRPD, supported decision making. This issue makes the researcher did a normative research by using some secondary data as regulations and also some conservatorship court judgment. Based on the research, the researcher found that the regulations and some conservatorship court judgment do not support the efforts to fulfill the rights of person with disabilities to got an equality before the law especially to make any decisions.